The Struggle: Violence Against Women in Spanish Universities. Issue 2 (August 2013) - Duque, Elena; Vidu, Ana; Schubert, Tinka
Violence against women in universities is an issue that was not studied in Spain until the pioneer research projects carried out by the CREA research center. Between 2008 and 2012, several studies were performed on this subject through competitive projects and dissertations. This article explains how these pioneer investigations, conducted with a communicative perspective demonstrate that gender violence also occurs in Spanish institutions, contrary to the prevailing wisdom of the university community. Once the problem has been identified, we discuss some of the consequences and the resistances encountered by victims and those who fight for a university free of violence against women when they make the issue visible and implement mechanisms to end it. Finally, we present some actions that are proving successful in overcoming the problem, as well as the first steps that are being taken in Spain in this regard.